2022
DOI: 10.3389/fonc.2021.755273
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Elastography: A Web-Based Nomogram Improves the Preoperative Prediction of Central Lymph Node Metastasis in cN0 PTC

Abstract: BackgroundGiven the difficulty of accurately determining the central lymph node metastasis (CLNM) status of patients with clinically node-negative (cN0) papillary thyroid carcinoma (PTC) before surgery, this study aims to combine real-time elastography (RTE) and conventional ultrasound (US) features with clinical features. The information is combined to construct and verify the nomogram to foresee the risk of CLNM in patients with cN0 PTC and to develop a network-based nomogram.MethodsFrom January 2018 to Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In this study, SRR was significantly higher in the CCLNM (+) group than in the CCLNM (-) group, and multivariate analysis showed that it was an independent predictor of occult CCLNM. Our results are similar to those of Huang et al., who reported that elasticity score on SUE was independently associated with CCLNM ( 29 ). They used a semi-quantitative parameter, whereas we preferred to use the quantitative SRR.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, SRR was significantly higher in the CCLNM (+) group than in the CCLNM (-) group, and multivariate analysis showed that it was an independent predictor of occult CCLNM. Our results are similar to those of Huang et al., who reported that elasticity score on SUE was independently associated with CCLNM ( 29 ). They used a semi-quantitative parameter, whereas we preferred to use the quantitative SRR.…”
Section: Discussionsupporting
confidence: 92%
“…Another approach taken to improve the detection of metastasis in CC-LN could be the combination of US and elastosonography [ 16 , 17 ]. In recent years, radiologists have focused on the development and validation of radiomic ultrasound nomograms as preoperative assessments of LN status in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Grayscale ultrasound of PTC reveals the lesion characteristics from a morphological viewpoint, CDFI reveals the characteristics of the blood flow distribution in the lesion area, and elastography provides information on the relative stiffness of the lesion. These imaging tests can be implemented as noninvasive ultrasound examinations (21), and the combined application of these tests may provide more imaging information and indirectly reflect more characteristics associated with tumor growth, invasiveness, and metastasis. To our knowledge, the combination of multimodal ultrasound features of primary PTC tumors and their use to develop a radiomics model to predict CLNM has not been reported.…”
Section: Introductionmentioning
confidence: 99%